Tradisi Lopis Raksasa dalam Perspektif Kerukunan Umat Beragama di Kota Pekalongan - Rosidin Rosidin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
This study aims to address the origin and the meaning for the community of tradition the â€œGiant Lopisâ€œ (Lopis Raksasa) in the perspective of religious harmony. The research has been conducted in a descriptive - qualitative approach. In this study, it is attempt to seek a thorough description and depth about the â€œGiant Lopisâ€ tradition. Furthermore, this study is to find out how the tradition plays a role in order to maintaining an harmony of community in Pekalongan municipality openly and naturally. The results of this study shows that, firstly, is that the tradition of the â€œGiant Lopisâ€ is closely associated with the practise of fasting on the Shawwal month, which was initiated by KH. Abdullah Siradj of Krapyak in 1855. Subsequently, his followers gave the guests whose came for silaturrahmi with snacks lopis on the 8th day. Another version mentioned that the lopis tradition was inspired by the speech of President Sukarno in 1950s in Kebon Rodjo Pekalongan. Secondly, glutinous rice as the basic ingredient lopis highlights a symbolic of the close relationship that tied rigging as a stronger. At this point, banana leaf wrapping is a symbol that people have to be usefull and good within their social life. Finally, the tradition of the giant lopis has a value of harmony, that is, to encourage tolerance, equality, and mutual cooperation.